PENGEMBANGAN MEDIA PEMBELAJARAN QUIZZIZ BERBASIS KEARIFAL LOKAL DALAM PEMBELAJARAN TEKS BERDASAR PADA KURIKULUM MERDEKA DI SMP DHARMA YADI MAKASSAR - Perawati, Ceceng; Rahim, Abd Rahman; Paida, Andi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Development of Quizziz Learning Media Based on Local Wisdom in Text Learning Based on the Independent Curriculum at Dharma Yadi Makassar Junior High School. This research aims to develop a digital learning media of procedural texts with a quizziz application based on local wisdom in grade VII junior high school students. This study uses the R&D (Research and Development) method with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. Research data was obtained through observation, interviews, and questionnaires. Data analysis was carried out by qualitative and quantitative analysis. The product feasibility test was carried out by Indonesian teachers and 10 grade VII students of SMP Dharma Yadi Makassar. The results obtained from the development of procedural text teaching materials with the quizziz application based on local wisdom in grade VII junior high school, received an assessment with very good criteria. The results of the validation of the assessment of Indonesian teachers received an average percentage of 93.3% and 94.4%, and the assessment of student responses received an average percentage of 89.2%. Thus, it can be concluded that the procedural text digital teaching material product with the quizziz application based on local wisdom for grade VII junior high school students is very feasible to be used in teaching and learning activities.